2022
DOI: 10.1155/2022/9102978
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA SCIRT Promotes HUVEC Angiogenesis via Stabilizing VEGFA mRNA Induced by Hypoxia

Abstract: Ischemia-reperfusion injury (IRI) is closely associated the abnormal expression of long noncoding RNAs (lncRNAs), especially for their regulatory roles in IRI-related angiogenesis. This study applied a hypoxia-reoxygenation (HR) cell model to simulate the IRI condition, as well as RNA sequencing and RNA pull-down experiments to reveal roles of the lncRNA and Stem Cell Inhibitory RNA Transcript (SCIRT), in endothelial angiogenesis. We found that SCIRT was increased under the HR condition and exhibited a high ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Previous research has suggested their relevance to heart diseases [26]. For example, VEGF-A is key in triggering cardiac angiogenic responses after acute myocardial infarction via regulating its interactors or downstream factors [27,28]. The results indicated that both endothelial cell-0 and endothelial cell-1 exhibited interactions with myocardial cells and fibroblasts involving receptors such as PDGFB_LRP1, PROS1_AXL, PDGFB_PDGFRA, PDGFB_PDGFRB, and PDGFB_ PDGFR (Fig.…”
Section: Analysis Of Cell Communication Centered On Fibroblasts and E...mentioning
confidence: 79%
“…Previous research has suggested their relevance to heart diseases [26]. For example, VEGF-A is key in triggering cardiac angiogenic responses after acute myocardial infarction via regulating its interactors or downstream factors [27,28]. The results indicated that both endothelial cell-0 and endothelial cell-1 exhibited interactions with myocardial cells and fibroblasts involving receptors such as PDGFB_LRP1, PROS1_AXL, PDGFB_PDGFRA, PDGFB_PDGFRB, and PDGFB_ PDGFR (Fig.…”
Section: Analysis Of Cell Communication Centered On Fibroblasts and E...mentioning
confidence: 79%
“…For example, in the kidney, VEGF is predominantly expressed in tubular epithelial cells, and VEGFR are mostly seen in cells of the preglomerular, glomerular and peritubular areas of the kidney. [ 67 ] Additionally, because it simultaneously increases microvascular permeability and contributes to endothelial cell migration, it has the potential to reduce IRI [ 68 ].…”
Section: Literature Searchmentioning
confidence: 99%
“…6 Hypoxia is a common pathological process of bone diseases, and osteoporosis results in local hypoxia in bone, affecting bone reconstruction, bone repair, and blood circulation. Hypoxia exposure attenuated the protein expression of CD31, 7 VEGFA, 8 and eNOS 9 in endothelial cells, which inhibits the proliferation, migration ability, and tube formation of endothelial cells. Therefore, up-regulating the expression of eNOS may be a key link in promoting angiogenesis.…”
Section: ■ Introductionmentioning
confidence: 96%